Effects of meteorological factors on outpatient visits for chronic rhinosinusitis in Wuhan, China (2018–2019): a time-series analysis - Xiaoli Guan; Wen Xiang; Ao Huang; Min Zhou; Ming Zeng (Frontiers in Public Health, 2025)
BackgroundStudies examining associations between meteorological factors and outpatient visits for chronic rhinosinusitis (CRS) are limited. This study aimed to investigate the effects of daily mean temperature, relative humidity (RH) and precipitation on outpatient visits for CRS.MethodsElectronic records of CRS outpatient visits were collected from Tongji hospital in Wuhan, China from January 1, 2018 to December 31, 2019. Daily meteorological data were obtained from the Wuhan Meteorological Bureau during the same period. A generalized additive negative binomial regression model combined with a distributed lag non-linear model (DLNM) was employed to analyze the lag-exposure-response relationship between meteorological factors and the number of CRS outpatient visits. Stratified analyses were conducted to identify potential effect modifications by age and season.ResultsA total of 14,259 CRS outpatient visits were recorded. Relative humidity and precipitation showed no significant association with daily CRS visits, whereas low temperatures significantly elevated CRS outpatient visits. Specifically, extreme temperature (−1.8°C, 1st percentile) was found to be associated with 1.946 (95% CI 1.273–2.973) times the risk of outpatient visits due to CRS, compared to the reference value of 32.9°C. Furthermore, the number of outpatient visits for childhood and younger individuals with CRS showed a negative correlation with temperatures, whereas middle-aged individuals and older adult individuals showed no such correlation.ConclusionThis study suggests that meteorological phenomena may have detrimental effects on health, thereby contributing to a better understanding of the environmental risk factors associated with this disease.